EKSPLORASI LAPANGAN JENIS PENGHASIL GAHARU (Gyrinops verstegii) DI PULAU LOMBOK NUSA TENGGARA BARAT - Sutomo Sutomo; Gebby Oktaviani (Fakultas Kehutanan Universitas Mulawarman, 2019)
High economic value encourages the hunt for agarwood in nature to increase and not be controlled so that the existence of agarwood becomes threatened and rare. Gyrinops versteegii (Gilg.) Domke is one example of agarwood-producing plants that are native to Indonesia and have different characteristics from other types so that it is preferred by consumers. Exploration and study of Gyrinops is very necessary, because information about Gyrinops is still very limited, especially to find out the population and its presence in nature and which has been cultivated by the community. The study of G. versteegii population was conducted in 7 locations in four districts namely West Lombok, North Lombok, East Lombok and Central Lombok conducted on 16-29 April 2018. There were 210 G. versteegii individuals found with 20 individual seedling growth stages, 54 individual saplings 98 individual poles and 38 individual trees. The location of the meeting is marked by its geographical location with the Global Positioning System (GPS). G. versteegii can be found in various environmental parameters, namely altitude 99 - 925 masl; slope 0 - 36.6 °; soil pH 5.5 - 6.6; soil moisture 50 - 95%; Light intensity 212 -> 20,000 Lux; air temperature 26.4 - 32.5 ° C and relative humidity 66.5 - 90%. G. versteegii that grows naturally can only be found at the Aikmel Resort in the Mount Rinjani National Park (TNGR) and there are only two individuals. Further exploration needs to be carried out in the area to determine the amount and conservation steps of G. versteegii remaining on the Island of Lombok.